THE VIEWS OF IDEA OF SOCIAL JUSTICE OF UKRAINIAN THINKERS OF LATE 19TH -EARLY 20TH CENTURIES - Макарова, А. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is devoted to research of applying the idea of social justice in the works of representatives of Ukrainian Philosophy of Late 19th -Early 20th centuries. The analysis is made in the context of reflecting the peculiarities of the interpretation of social justice in the historical Ukrainian tradition of philosophizing in Ukrainian Philosophy. In the structure of philosophical panorama highlighted of semantic trends, revealing political, economic, religious, ethic and legal aspects of social justice as opposite in their specific character. During the research two groups of thinkers, who developed the idea of social justice, were singled out: social-political thinkers, representing the philosophical-public movement and representatives of professional-academic philosophy (all belong to the teaching staff of St.Volodymyr Kyiv University and Kiev Spiritual Academy). In the philosophic understanding of interpreting the idea of social justice there have been found both different and similar features.